2012
DOI: 10.5923/j.ijaf.20120204.03
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships of <i>Santalum album</i> and its Adulterants as Inferred from Nuclear DNA Sequences

Abstract: The East Indian sandalwood, Santalum album, valued for its fragrant oil yielding heartwood is a major ingredient in indigenous medicines and perfumes. Scarcity of sandal has led to illegal felling of sandal trees, and adulteration of sandalwood and oil. This study represents the first molecular phylogeny of S. album and its adulterant species Osyris wightiana, Erythroxylum monogynum, Buxus sempervirens, Ximenia americana, Osyris lanceolata, and Chukrasia tabularis through 18S and 26S rDNA sequencing. In the Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Several studies has reported the adulteration of Stephania tetrandra (Fang-Ji) roots with roots of the toxic herb, Aristolochia fangchi (Guang-Fang-Ji) leading to major renal failure (Jadot et al 2017;Michl et al 2013). Similarly, Mesua ferrea was adulterated with Calophyllum inophyllum (Poornima 2010), Piper nigrum with Lantana camara and Embelia ribes (Dhanya and Sasikumar 2010), Papavar somniferum with Amaranthus paniculatas (Dhanya and Sasikumar 2010), Santalum album with Erythroxylum monogynum (Chembath et al 2012), Gloriosa superba with Ipomea species (Kumar et al 2018) as well as Cassia fistula was adulterated with Senna auriculata (Seethapathy et al 2015). In 2002, the US Food and Drug Administration received several reports of liver-related injuries such as hepatitis, cirrhosis, and liver failure due to consumption of Piper methysticum containing products which was subsequently banned in Germany, Switzerland, France, Canada and UK (US Food and Drug Administration 2001).…”
Section: Raw Drug Adulterationmentioning
confidence: 99%
“…Several studies has reported the adulteration of Stephania tetrandra (Fang-Ji) roots with roots of the toxic herb, Aristolochia fangchi (Guang-Fang-Ji) leading to major renal failure (Jadot et al 2017;Michl et al 2013). Similarly, Mesua ferrea was adulterated with Calophyllum inophyllum (Poornima 2010), Piper nigrum with Lantana camara and Embelia ribes (Dhanya and Sasikumar 2010), Papavar somniferum with Amaranthus paniculatas (Dhanya and Sasikumar 2010), Santalum album with Erythroxylum monogynum (Chembath et al 2012), Gloriosa superba with Ipomea species (Kumar et al 2018) as well as Cassia fistula was adulterated with Senna auriculata (Seethapathy et al 2015). In 2002, the US Food and Drug Administration received several reports of liver-related injuries such as hepatitis, cirrhosis, and liver failure due to consumption of Piper methysticum containing products which was subsequently banned in Germany, Switzerland, France, Canada and UK (US Food and Drug Administration 2001).…”
Section: Raw Drug Adulterationmentioning
confidence: 99%